2012
DOI: 10.1002/lary.22495
|View full text |Cite
|
Sign up to set email alerts
|

Inverted papilloma of the nasal cavity and paranasal sinuses: A Korean multicenter study

Abstract: Generally, there were no significant differences in recurrence rates according to clinical stage or surgical approach. Given the rate of delayed recurrence, follow-up of >3 years is required. Moreover, surgeons should always consider combined approaches to reduce the chances of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
131
5
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(152 citation statements)
references
References 15 publications
11
131
5
5
Order By: Relevance
“…An association between Krouse stage system and recurrence of SIP was not identified in a recent study involving 156 SIP patients (19). In a multicenter study involving 578 SIP patients, three stage systems (the Krouse staging system, the Furuta staging system and the Cannady staging system) did not associate with SIP recurrence rates (2). This study also suggested that patients with advanced stage of SIP who underwent single endoscopic surgery presented a higher recurrence rate.…”
Section: Clinical Risk Factors For Sip Recurrencementioning
confidence: 70%
See 4 more Smart Citations
“…An association between Krouse stage system and recurrence of SIP was not identified in a recent study involving 156 SIP patients (19). In a multicenter study involving 578 SIP patients, three stage systems (the Krouse staging system, the Furuta staging system and the Cannady staging system) did not associate with SIP recurrence rates (2). This study also suggested that patients with advanced stage of SIP who underwent single endoscopic surgery presented a higher recurrence rate.…”
Section: Clinical Risk Factors For Sip Recurrencementioning
confidence: 70%
“…A study of 212 SIP patients demonstrated that SIP lesions with an extensive involvement of the frontal sinus and/or supraorbital cell may require a combined approach (25). In addition, the Korean multicenter study suggested that surgeons should consider combined approaches to reduce recurrence for advanced SIP [Krouse staging system: T3 stage (12); Furuta staging system: T3-A stage (13); Cannady staging system: group B (14)], particularly for novice surgeons (2). Although certain authors propose that SIP involving attachment sites within the maxillary sinus require a endoscopic-external combined technique (1,26), emerging evidence suggests that novel tailored ESS techniques (endoscopic modified medial maxillectomy, and transnasal endoscopic anterior and medial maxillectomy) allow enhanced visualization and preserve important structures, including the inferior turbinate and nasolacrimal duct (27)(28)(29).…”
Section: Clinical Risk Factors For Sip Recurrencementioning
confidence: 99%
See 3 more Smart Citations